Difficulties of nurses in the management of the hospital's emergency room - Thais Vanessa Bugs; Denise de Fátima Hoffmann Rigo; Cristina Daiana Bohrer; Fabieli Borges; João Lucas Campos de Oliveira; Nelsi Salete Tonini (Universidade Federal de Santa Maria, 2017)
Aim: to identify the difficulties of the nurse in the management of the Emergency Room. Method: descriptive, qualitative and documentary study. It was developed through the portfolios of nursing residents about the management work of nurses from abril to june 2016 in the emergency room of a public university hospital in the interior of Paraná, Brazil. Content Analysis in the thematic mode was used to analyse the records of observations and portfolio. Results: three categories, which are related to the difficulties in emergency room operation dynamics, managing people and managing material resources, emerged. Conclusion: the difficulties experienced ratify the management contingency and complexity, which sometimes surpass the nurses' governance. However, especially in the resources management, it is necessary that the professional uses the management tools more rationally, aiming a qualified care